Iran’s Transition to Wind Energy - Sh. Nourifard (Renewable Energy Research and Applications, 2021)
In this article, three topics of wind energy science, wind energy engineering and wind energy policy of Iran have been discussed. Deciding on wind energy in the country requires comprehensive information in these three areas. Due to the increase in the capacity of renewable energy in neighboring countries and global energy transition, as well as the high potential of Iran in the field of renewable energy, especially wind energy, its culture in the country and the transfer of concepts in simple language is necessary.